ChemInform Abstract: Rapid Synthesis of Isoquinolinones by Intramolecular Coupling of Amides and Ketones. Issue 21 (May 2015) - Wei, Wen‐Tao; Liu, Yu; Ye, Lin‐Miao; Lei, Rong‐Hui; Zhang, Xue‐Jing; Yan, Ming
Abstract Amides and ketones are intramolecularly coupled in the presence of KOtBu in DMF.